O desenvolvimento do julgamento moral e a educação de valores na disciplina de ensino religioso - Sebben, Kelly Sartori (2007)
This research is characterized by a theological analysis of the texts of Jayme Caetano Braun, who is a southern Brazilian traditional poet Galpão de Estância (1954), De Fogão em Fogão (1958), Brasil Grande do Sul and Paisagens Perdidas (1966) , associating the literary theory of semiotics and the theology of culture. In the first chapter, the theoretical referential of Paul Tillich s theology of culture is introduced, starting from the presumption that religion is the foundation of culture and its task is to lift the deep substance to the surface. Yet in this chapter, using Jakobson and Lotman, the establishment of literary semiotics as a helping tool in this hermeneutic task is sought. The second chapter relates the results of an investigation of the main works about theology and literature produced in Brazil. Finally, in the third and last chapter, Jayme Caetano Braun s works are situated in the context of southern Brazilian poetry. Starting from a thematic division, the literary semiotic analysis proceeds in order to establish a theological vision about the theme.